Using the Theory of Planned Behaviour to design a food hygiene intervention - Mullan, Barbara; Wong, C. (Pergamon, 2010)
Twenty percent of food poisoning annually in Australia is believed to result from consumer food handling behaviour. Research advocates the use of social cognition theories in designing food hygiene interventions, however very few studies have actually done so. Thus, this study investigated the efficacy of a food hygiene intervention based on the Theory of Planned Behaviour (TPB). One hundred and eighty-four participants completed a TPB questionnaire, including questions regarding past behaviour and food hygiene knowledge, and then were randomly allocated to a knowledge and implementation intention group, a combined knowledge/implementation intention/PBC group, or a control group. Behaviour was measured 4 weeks later. The TPB predicted a high proportion of variance in both intentions and behaviour, but neither intervention improved participants’ food hygiene behaviours. However, knowledge and PBC were significantly increased in the PBC group. The implications of this for future research are explored.